Application of artificial neural network in predicting crop yield: a review - Bejo, Siti Khairunniza; Mustaffha, Samihah; Wan Ismail, Wan Ishak (David Publishing Company, 2014)
Agricultural system is very complex since it deals with large data situation which comes from a number of factors. A lot of techniques and approaches have been used to identify any interactions between factors that affecting yields with the crop performances. The application of neural network to the task of solving non-linear and complex systems is promising. This paper presents a review on the use of artificial neural network (ANN) in predicting crop yield using various crop performance factors. General overview on the application of ANN and the basic concept of neural network architecture are also presented. From the literature, it has been shown that ANN provides better interpretation of crop variability compared to the other methods.